1991
DOI: 10.1203/00006450-199109000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Characterization of Variant Long-Chain Acyl-CoA Dehydrogenase in Cultured Fibroblasts from Nine Patients with Long-Chain Acyl-CoA Dehydrogenase Deficiency

Abstract: ABSTRACT. Long-chain acyl-CoA dehydrogenase (LCAD) deficiency is a disorder of mitochondria1 fatty acid oxidation that is characterized by hypoglycemia, muscle weakness, and hepato-and cardiomegaly. To characterize variant LCAD, we first carried out preliminary experiments using pure enzyme preparations. Despite the significant sequence similarity of LCAD to medium-chain acylCoA dehydrogenase, the antibody raised against rat LCAD was monospecific for human and rat LCAD and did not cross-react with either human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Microscopic examination of autopsy tissues revealed severe macrovesicular lipid storage in heart, liver, kidneys, and skeletal muscle. Patients 3, 4, and 5 were initially reported as having LCAD deficiency (12,13,25,26), but later, were shown to be deficient in VLCAD, rather than in LCAD, using immunoblot analysis (23). Patient 6 was reported previously to have LCAD deficiency (12,13), but has been found to be deficient in VLCAD in this study.…”
Section: Case Historycontrasting
confidence: 37%
See 3 more Smart Citations
“…Microscopic examination of autopsy tissues revealed severe macrovesicular lipid storage in heart, liver, kidneys, and skeletal muscle. Patients 3, 4, and 5 were initially reported as having LCAD deficiency (12,13,25,26), but later, were shown to be deficient in VLCAD, rather than in LCAD, using immunoblot analysis (23). Patient 6 was reported previously to have LCAD deficiency (12,13), but has been found to be deficient in VLCAD in this study.…”
Section: Case Historycontrasting
confidence: 37%
“…The case histories were partially described in the previous reports (12,13,22,(24)(25)(26). We describe them as follows.…”
Section: Case Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the diagnosis of LCAD deficiency has been made based on the reduced dehydrogenase activity toward palmitoyl-CoA in the soluble cell fraction of cells such as fibroblasts or leukocytes (9). Recently, we reported that, among nine LCAD-deficient cell lines, all exhibited a positive protein band that was immunoreactive with anti-LCAD antibody, had a normal molecular mass and normal intensity (10). This result appeared to suggest that all cases of LCAD deficiency were caused by a point mutation in the LCAD gene.…”
mentioning
confidence: 76%